PENGARUH TINGKAT UPAH TERHADAP PRODUKTIVITAS TENAGA KERJA DI INDONESIA - B01111073, SYAINI (Jurnal Pembangunan dan Pemerataan, 2016)
Productivity is essentially an input factor effectiveness in generating output. Increasing the amount of labor that is not accompanied by an increase in the performance of the worker will affect the production process and will ultimately hamper economic growth. This research seeks to analyze the effect of the level of wages on labor productivity in Indonesia period 2006-2013 . To answer these objectives is to analyze the effect of the level of wages on labor productivity in Indonesia , used Simple Linear Regression analysis tool . The data used in this research is secondary data drawn from the BPS. Research results revealed positive influence on the wage rate of labor productivity in Indonesia . The wage rate has a positive and significant impact on labor productivity . Individual variable salary has a positive and significant relationship to productivity of labor in Indonesia . From the analysis it can be concluded the greater the province minimum wage and average wage / salary given and is owned by the workers , the greater the level of labor productivity. Â  Â  Keywords : UMP rate , average wage / salary , Labor Productivity .